PENYUSUNAN DATA BASE PERUMAHAN DALAM MEWUJUDKAN TATA KELOLA YANG EFEKTIF DAN EFISIEN DI KABUPATEN MADIUN - mahmud rizal irawan (Birokrasi Pancasila: Jurnal Pemerintahan, Pembangunan dan Inovasi Daerah, 2022)
Excellent local government service to the community is dreamed of, in this case, housing and settlement services that are well managed. The database preparation is intended to determine policies, planning, development, control, monitoring, and evaluation of housing and settlement development in the Madiun Regency. The research objective is to compile a housing database in Madiun Regency to realize effective and efficient governance. The research was conducted using primary and secondary data survey methods in the target areas in 15 sub-districts. The data observed were the number of housing units, ownership status, number of uninhabitable houses, number of commercial houses, disaster-prone areas, and number of buildings with IMB and electricity networks. The analysis was carried out by tabulating primary and secondary data. The results showed that the number of houses in Madiun District was 249,357 units, ownership status was 86.56% self-owned, and the number of houses unfit for habitation was 17.15% commercial houses were 106 housing estates, and the main disaster-prone areas were floods, landslides, and fires. -IMB 4.85% and electricity network 99.77%. Moreover, disaster-prone areas are dominated by fires at 49.09% and floods at 26.36%.Keywords; database, housing, ownership, livable